Women’s voices in tourism research. Contributions to knowledge and letters to future generations - Mantecón Terán, Alejandro (Investigaciones Turísticas, 2022)
Reseña del libro de Antonia Correia y Sara Dolnicar (eds.) (2021): Women’s voices in tourism research. Contributions to knowledge and letters to future generations. Brisbane: The University of Queensland. E-Book ISBN: 978-1-74272-365-5. https://doi.org/10.14264/817f87d